Direct quantification of total sulfur dioxide in wine using triple quadrupole ICP-MS. Issue 7 (12th March 2015) - Wang, Xiao-wei; Liu, Jing-fu; Wang, Xiao-yan; Shao, Bing; Liu, Li-ping; Zhang, Jing
Abstract : The unanimous ionization efficiency of various S-containing compounds indicates the great convenience for determination of total SO2 in wine via ICP-QQQ. Abstract : The accurate determination of sulfur dioxide (SO2 ) in wine remains a critical analytical task for food safety and in wine trade. The traditional recommended titration method has been criticized for its weak selectivity, poor precision and long procedure. In this study, an accurate, high-throughput, interference-free method for the absolute determination of SO2 in wine based on a triple quadrupole ICP-MS instrument (ICP-QQQ) is developed. This novel ICP-QQQ is operated in the MS/MS mode to provide an interference-free measurement. Tested with four different S-containing inorganic ions and organic molecules, the result indicates that the behaviour of S in the plasma is unanimous regardless of the discrepancy between the S-containing compounds, which means the signal intensity of S is merely decided by the concentration of S. The developed method exhibits good linearity ( R > 0.999) over the concentration range of 0.025–100 mg L −1, with a limit of quantification of 10 μg L −1 for 32 S 16 O4 2− in wine. The recoveries ranged from 95–105% for the spiked wine samples. The method was successfully applied for the determination of total SO2 in red wine samples. The concentrations determined using the developed method are in excellent agreement with those obtained using the recommended titration method. This study demonstrates a new approach for the quantification of total SO2 in wine with great convenience and high accuracy.